Political Parties and Elections in Brazil’s State of Rio Grande do Norte (1982-2014): institutionalization and relative stability - da Silva, Marcos Antônio (Revista de Ciências Sociais, 2016)
This study aimed to understand the electoral performance of political parties in Rio Grande do Norte (RN), since the transition from military rule (1982) until 2014. In this regard, it is clear that the party state system was structured in his early years around two parties, PDS and PMDB, following the national standard. In the late 80's and early next, the electoral system has become highly fragmented, with the predominance of center parties (PMDB, PSDB), center-right (PTB) and right (DEM / PFL). With the rise of the center-left (PDT, PT, PSB), in the late 90s, the party potiguar system seems to acquire a relative stability. This analysis discusses also the decisive influence of the state executive and oligarchies (Maia, Alves and Rosado, among others) and, to a lesser extent, from the federal to the structuring of the party state system.